Cork oak (Quercus suber L.) seedlings acclimate to elevated CO2 and water stress: photosynthesis, growth, wood anatomy and hydraulic conductivity (Trees, 2012)
Leaf gas-exchange, leaf and shoot anatomy, wood density and hydraulic conductivity were investigated in seedlings of Quercus suber L. grown for 15 months either at elevated (700 lmol mol -1 ) or normal (350 lmol mol -1 ) ambient atmospheric CO2 concentrations. Plants were grown in greenhouses in a controlled environment: relative humidity 50% (±5), temperature similar to external temperature and natural light conditions. Plants were supplied with nutrients and two water regimes (WW, well watered; WS, water stress). After 6 months exposure to CO2 enrichment an increase in photosynthetic rate, a decrease in stomatal conductance and a decrease in carbon isotope discrimination (D 13 C) were observed, along with enhanced growth and an increase in the number of branches and branch diameter. Over the same period, the shoot weight ratio increased, the root weight ratio decreased and the leaf weight ratio was unaffected. The speciﬁc leaf area increased due to an increase in total leaf thickness, mainly due to the palisade parenchyma and starch. However, after 9 and 15 months of elevated CO2 exposure, the above-mentioned physiological and morphological parameters appeared to be unaffected. Elevated CO2 did not promote changes in vessel lumen diameter, vessel frequency or wood density in stems grown in greenhouse conditions. As a consequence, xylem hydraulic efﬁciency remained unchanged. Likewise, xylem vulnerability to embolism was not modiﬁed by elevated CO2. In summary, elevated CO2 had no positive effect on the ecophysiological parameters or growth of water stressed plants.

Methanolysis of bark suberins: analysis of glycerol and acid monomers (Phytochemical Analysis, 2000)
The depolymerization and subsequent analysis of cork suberins from the outer barks of Pseudotsuga menziesii and Quercus suber was performed using a simpliﬁed methanolysis procedure. The amount of sodium methoxide catalyst was maintained at 20–30 mM and the methanolysis mixture was submitted to trimethylsilyl derivatisation and used directly for gas chromatographic analysis, allowing simultaneous quantiﬁcation of glycerol and long-chain monomers. Response factors for glycerol, ferulic acid and one saturated homologue representing each of the suberinic families (i.e. the 1-alkanols, 1-alkanoic acids, vhydroxyacids and a,v-diacids) were determined. Effective depolymerization of suberin was checked using the infrared specta of the residues after methanolysis. Glycerol is a major constituent of the suberins from P. menziesii (26% of total) and from Q. suber (14%). In both suberins, a,v-diacids are dominant, i.e. 54% of the long-chain monomers in P. menziesii (mostly saturated C16-C22 homologues and the C18 unsaturated diacid), and 53% in Q. suber (mostly the C18 unsaturated diacid and mid-chain oxygenated (epoxide and vic-diol) derivatives). In P. menziesii epoxyacids are absent. The importance of glycerol and a,v-diacids as suberin monomers supports a polymeric structure based on their successive esteriﬁcation.

THE EFFECT OF GROWTH-RATE ON THE STRUCTURE AND COMPRESSIVE PROPERTIES OF CORK (IAWA BULLETIN, 1992)
Cork samples with an age of 9 years and with different growth rates, corresponding to calibre classes `small', `medium' and `large', were observed by scanning electron microscopy and tested mechanically in compression. Differences in calibre correspond to different widths of annual growth rings; widths differ because both the number of cells produced per year and cell dimensions differ. For instance, small and large calibre cork had, respectively, 50 and 151 cells in one row of an annual growth ring, with an average prism height of 32.6 and 39.8 mum. The stress-strain curves obtained in compression parallel to the three main directions showed that cork with the higher growth rate (large calibre) has lower strength in compression for all strains and lower Young's moduli.